Mexican interview (2001) - Toledo, Alejandro (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The Larva phenomenon began to take shape during the seventies in the old and now defunct Mexican magazine Plural, directed by Octavio Paz. The first fragment of that (in)finite work in progress was published there, a novel in corso and ricorso, that has several chapters: Babel de una noche de San Juan (1984), Poundemonium (1986), La vida sexual de las Palabras (1991), Sombreros para Alicia (1993), Amores que atan o Belles Lettres (1995), Álbum de Babel (1995), Monstruario (1999) and Puente de Alma (2009). This conversation took place in Mexico City in 2001.
Keywords: Julián Ríos; interview; Larva; avant-garde; literary field; critique; tradition; modernity